Competing with Media Richness: Cognitive and Psychological Endowment Effects as the Fundamentally Pervasive Perspective of Learning Performance - Sumiyana Sumiyana; Muhammad Adlin Saputra (Human Behavior and Emerging Technologies)
This study investigates the students’ behaviour, especially regarding their cognitive and psychological endowments’ effect on their cognitive absorption, attachment comprehensivity, and learning achievement through various types of learning media. Specifically, it highlights that the resulting learning performance fundamentally starts from individual endowment positions, regardless of the available types of learning media. The authors find that the cognitive and psychological endowments’ functional superiority dominates the learning achievement compared to the MR role types. Furthermore, we demonstrate that individuals’ beliefs, attitudes, and behaviour are superior to their cognitive and psychological endowments because motivation, inner spirit, and faithfulness in appropriation defeat their material knowledge acquisition in their learning processes, such as absorption, achievement, and attachment. This research presents its novelty through learning attachment behaviour due to supremely personal psychological and cognitive endowment effects. Furthermore, the students with the highest negative experiences impact low absorption, comprehensive attachment, and learning achievement. Finally, the authors reveal that individually endowed mindsets and attitudes contribute to higher learning performance than the MR role types. Thus, it demonstrates that the MR role types produce a low incremental performance, which is nothing more than maximising valuable information.